History and Myth in Romanian Consciousness - Lucian Boia (Book collections on Project MUSE., 2001)
Based on the idea that there is a considerable difference between reality and discourse, the author points out that history is constantly reconstructed, adapted and sometimes mythicized from the perspectives of the present day, present states of mind and ideologies. He closely examines historical culture and conscience in nineteenth and twentieth century Romania, particularly concentrating on the impact of the national ideology on history. Boia's innovative analysis identifies several key myt ...